2000
DOI: 10.1164/ajrccm.161.1.9904080
|View full text |Cite
|
Sign up to set email alerts
|

Capnometric Recirculation Gas Tonometry and Weaning from Mechanical Ventilation

Abstract: The aim of this study was to describe changes in regional intramucosal PCO(2) (Pr(CO(2)) measured with capnometric recirculation gas tonometry [CRGT]) in patients with acute respiratory failure, who proceed from mechanical ventilation to weaning. In addition, we compared the predictive power for the weaning outcome of CRGT measurements obtained during mechanical ventilation to the frequency/ tidal volume (f/VT) ratio. A total of 24 patients (31 weaning trials) were included in the study, but four of the 24 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 30 publications
0
13
1
2
Order By: Relevance
“…10 f/V T is significantly higher in patients who failed weaning. [21][22][23] Although there was no significant difference in weaning rate between the 2 groups, chair-sitting training was associated with a significant f/V T increase in our patients. Chair-sitting training, therefore, had no benefit on our patients' respiratory muscle function and might induce an increase in mechanical load to breathe in mechanically ventilated ICU patients.…”
Section: Discussioncontrasting
confidence: 54%
“…10 f/V T is significantly higher in patients who failed weaning. [21][22][23] Although there was no significant difference in weaning rate between the 2 groups, chair-sitting training was associated with a significant f/V T increase in our patients. Chair-sitting training, therefore, had no benefit on our patients' respiratory muscle function and might induce an increase in mechanical load to breathe in mechanically ventilated ICU patients.…”
Section: Discussioncontrasting
confidence: 54%
“…Leitch et al (22) stated that 20.9% of their patients required noninvasive ventilatory assistance after extubation. Some investigators (47)(48)(49) consider such patients to represent extubation failure; the Task Force did not mention this consideration.…”
Section: Systematic Errormentioning
confidence: 99%
“…Previous studies have reported that early indirect parameters of cardiac function, such as capnometric recirculation gas tonometry and gastric intramucosal pH, were altered in patients who presented with failure to wean from mechanical ventilation. These findings can be explained by the likelihood that the increased respiratory workload during spontaneous test breathing can induce an intestinal mucosa hypoperfusion because of the adrenergic response and effort required to increase the blood flow to the respiratory muscles (31-33). Similarly, the BNP levels during the spontaneous breathing test might help physicians identify earlier those patients with postoperative heart failure and support decisions to discontinue mechanical ventilation after cardiac surgery, potentially decreasing the risk of weaning failure (6,18,21).…”
Section: Discussionmentioning
confidence: 99%